2016
DOI: 10.1155/2016/3494608
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Cellular and Molecular Inflammatory Mediators in Lung Cancer

Abstract: Inflammation is a component of the tumor microenvironment and represents the 7th hallmark of cancer. Chronic inflammation plays a critical role in tumorigenesis. Tumor infiltrating inflammatory cells mediate processes associated with progression, immune suppression, promotion of neoangiogenesis and lymphangiogenesis, remodeling of extracellular matrix, invasion and metastasis, and, lastly, the inhibition of vaccine-induced antitumor T cell response. Accumulating evidence indicates a critical role of myeloid ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 127 publications
(129 reference statements)
0
24
0
3
Order By: Relevance
“…In Latin America, it is also worth mentioning that the ideal treatment options for advanced NSCLC remain elusive [29]. First of all, organized strategies for screening, diagnosis, and treatment are generally not implemented; second, there is very limited access to target therapies due to high prices, lack of insurance, or for social reasons; and finally, screening for specific mutations is not routinely performed [19, 30].…”
Section: Discussionmentioning
confidence: 99%
“…In Latin America, it is also worth mentioning that the ideal treatment options for advanced NSCLC remain elusive [29]. First of all, organized strategies for screening, diagnosis, and treatment are generally not implemented; second, there is very limited access to target therapies due to high prices, lack of insurance, or for social reasons; and finally, screening for specific mutations is not routinely performed [19, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory mediators are known to play crucial roles in tumor progression by regulating not just the immune infiltrations in tumors but also by playing the important role in invasion and metastasis [20, 21]. A number of studies have demonstrated that CXCR2 plays a pivotal role in tumor angiogenesis, proliferation, and invasion [8, 22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory cells that contribute to this phenotype are multi-faceted and include macrophages, neutrophils, and T cells, among others [11]. In addition, there is evidence that malignant epithelial cells can also secrete inflammatory cytokines [12].…”
Section: Introductionmentioning
confidence: 99%